Use of Action Research in Nursing Education - Susan D. Moch; R. Todd Vandenbark; Shelley-Rae Pehler; Angela Stombaugh (Nursing Research and Practice)
Purpose. The purpose of this article is to describe action research in nursing education and to propose a definition of action research for providing guidelines for research proposals and criteria for assessing potential publications for nursing higher education. Methods. The first part of this project involved a search of the literature on action research in nursing higher education from 1994 to 2013. Searches were conducted in the CINAHL and MEDLINE databases. Applying the criteria identified, 80 publications were reviewed. The second part of the project involved a literature review of action research methodology from several disciplines to assist in assessing articles in this review. Results. This article summarizes the nursing higher education literature reviewed and provides processes and content related to four topic areas in nursing higher education. The descriptions assist researchers in learning more about the complexity of both the action research process and the varied outcomes. The literature review of action research in many disciplines along with the review of action research in higher education provided a framework for developing a nursing-education-centric definition of action research. Conclusions. Although guidelines for developing action research and criteria for publication are suggested, continued development of methods for synthesizing action research is recommended.